2002
DOI: 10.14411/fp.2002.006
|View full text |Cite
|
Sign up to set email alerts
|

Kudoa dianae sp. n. (Myxosporea: Multivalvulida), a new parasite of bullseye puffer, Sphoeroides annulatus (Tetraodontiformes: Tetraodontidae)

Abstract: Abstract.A new multivalvulid myxosporean species, Kudoa dianae sp. n., is described from bullseye puffer, Sphoeroides annulatus (Jenyns) (Tetraodontiformes: Tetraodontidae). Plasmodia develop in extramuscular sites, in the wall of oesophagus and less frequently on mesenteries. Mature spores can reach lumen of the digestive tract directly by disruption of plasmodial wall or via macrophage transport to the oesophageal epithelium. New species is characterised by morphology of spores and by the complete sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
5
18
0
1
Order By: Relevance
“…The comparisons between present material and all the other species in extra-muscular locations showed that they do not match any of the descriptions, despite some similarities relating to hosts and parasite location within the host. Kudoa dianae Dyková, et al 2002, was more similar to our specimens and has been found infecting Sphoeroides annulatus in Mexico (DYKOVÁ et al, 2002). This species is also located on the wall of the esophagus.…”
Section: Discussionsupporting
confidence: 79%
“…The comparisons between present material and all the other species in extra-muscular locations showed that they do not match any of the descriptions, despite some similarities relating to hosts and parasite location within the host. Kudoa dianae Dyková, et al 2002, was more similar to our specimens and has been found infecting Sphoeroides annulatus in Mexico (DYKOVÁ et al, 2002). This species is also located on the wall of the esophagus.…”
Section: Discussionsupporting
confidence: 79%
“…e Ultrathin section of the spore with polar filament (PF) extruded from large polar capsule (PC). Scale bars: a=0.2 mm, b=0.1 mm, c=2.0μm, d=4.8μm, e=1.0μm the intestine and from the pyloric caeca of mullets from commercial fish of the Indian and the Pacific Oceans (Sarkar and Chaudhury 1996;Tripathi 1951;Dykova et al 2002;Egusa and Shiomitsu, 1983). The spore morphology of K. unicapsula n. sp.…”
Section: Resultsmentioning
confidence: 99%
“…The list of species belonging to this genus was expanded to 52, with 5 new species described recently (Moran et al 1999, Dyková et al 2002, Whipps et al 2003a,b, Cho & Kim 2003. Certain species are of economic concern to aquaculture and commercial marine fisheries because they either cause unsightly pseudocysts in the muscle or they produce postmortem myoliquefactive autolysis, also known as 'soft flesh', when the fish is stored at high temperatures (Moran et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…K. rosenbuschi is clustered with K. clupeidae and K. funduli, which are species collected from different host species of the Atlantic coast, but it is also closely related with Kudoa species collected from fishes of the Pacific coast. Nevertheless, Dyková et al (2002) suggested that it might be necessary to use other molecular approaches, due to the low bootstrap values of the phylogenetic tree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation